Does value-based purchasing affect US hospital utilization pattern: A comparative study. (3rd April 2019) - Hamadi, Hanadi; Spaulding, Aaron; Haley, D. Rob; Zhao, Mei; Tafili, Aurora; Zakari, Nazik
ABSTRACT: We evaluated the effect US hospital performance as measured by the Medicare hospital value-based purchasing (HVBP) program has on the volume of hospitals inpatient and outpatient services. We analyzed data from the 2013 to 2014 American Hospital Association database, HVBP total performance scores database through Centers for Medicare and Medicaid Services (CMS) and the area health resources files database through CMS. This study utilized a multinomial logistic regression and transaction cost economic theory, adjusting for the Herfindahl–Hirschman Index, number of facility beds, beds per thousand, individuals 65+, teaching status, location, ownership, and system affiliation. The prominent study findings indicate a significant relationship between percent utilization of inpatient, outpatient and HVBP score. Furthermore, environmental factors such as the Herfindahl–Hirschman Index, and system participation were found to significantly impact hospitals ratio of inpatient to outpatient. Relative risk ratios show that hospitals with overall lower HVB are more likely to be in the top 25 percentile for outpatient services. With the decline in inpatient volume of services and the rise in outpatient utilization, inpatient metrics will continue to be relevant as key indicators of quality of care. Inpatient services will never become irrelevant to the overall financial profile of hospital performance.